Unsustainable Development in the Mekong: The Price of Hydropower - Ho, Ezra (Consilience, 2014)
Since the first Earth Summit, “sustainable development” has entered the lexicon of development and global change. However, far from being useful in guiding socially and environmentally sensitive development, sustainable development has remained an elusive notion. The recent conceptualisation of a set of Sustainable Development Goals (SDG), replacing the Millennium Development Goals (MDG) shows promise of a framework to unify and operationalise the concept of “sustainable development”. Examining hydropower development in the socially diverse and ecologically complex Mekong River basin, I illustrate the challenges for sustainable development. By using the SDG framework, I highlight the unsustainable trajectory of development in the Mekong basin.